Impact of familiarity and gender differences on the stigmatisation of children with mental illness, and their parents - Cheong, Sau Kuan * (Sunway University College, 2009)
The aim of this study is to investigate the impact of familiarity and gender differences on the stigmatisation of children with mental illness, and their parents. A total of 234 participants took part in a study to ascertain stigmatisation of children with mental illness, and parents who have a child with mental illness. This study measured the attitudes of participants who have different levels of familiarity with the mentally-ill people and compared the attitudes of these people based on gender. All participants completed self-reported questionnaires about their attitudes towards stigmatisation and their levels of familiarity with people with mental illness. The results indicated that participants with a lower level of familiarity tended to have a higher level of segregation from children with mental illness. Females have a higher level of sympathy for parents who have a child with mental illness.